Formation of 6-, 8- and 10-shogaol in ginger through application of different drying methods: altered antioxidant and antimicrobial activity - Ghasemzadeh, Ali; Jaafar, Hawa Z. E.; Baghdadi, Ali; Tayebi-Meigooni, Amin (MDPI, 2018)
Gingerols and shogaols are compounds found in ginger (Zingiber officinale Roscoe); shogaols are found in lower concentration than gingerols but exhibit higher biological activities. This work studied the effects of different drying methods including open sun drying (OSD) solar tunnel drying (STD) and hot air drying (HAD) with various temperature on the formation of six main active compounds in ginger rhizomes, namely 6-, 8-, and 10-gingerols and 6-, 8-, and 10-shogaols, as well as essential oil content. Antioxidant and antimicrobial activity of dried ginger was also evaluated. High performance liquid chromatography (HPLC) analysis showed that after HAD with variable temperature (120, 150 and 180 °C), contents of 6-, 8-, and 10-gingerols decreased, while contents of 6-, 8-, and 10-shogaol increased. High formation of 6-, 8-, and 10-shogaol contents were observed in HAD (at 150 °C for 6 h) followed by STD and OSD, respectively. OSD exhibited high content of essential oil followed by STD and HAD method. Ginger-treated with HAD exhibited the highest DPPH (IC50 of 57.8 mg/g DW) and FRAP (493.8 µM of Fe(II)/g DM) activity, compared to STD and OSD method. HAD ginger exhibited potent antimicrobial activity with lower minimum inhibition concentration (MIC) value against bacteria strains followed by STD and OSD, respectively. Ginger extracts showed more potent antimicrobial activity against Gram positive bacteria than Gram negative bacteria strains. Result of this study confirmed that conversion of gingerols to shogaols was significantly affected by different drying temperature and time. HAD at 150 °C for 6 h, provides a method for enhancing shogaols content in ginger rhizomes with improving antioxidant and antimicrobial activities.